2001
DOI: 10.1046/j.1365-2141.2001.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability occurs in defined subsets of patients with acute myeloblastic leukaemia

Abstract: Summary. Using a sensitive fluorescent-polymerase chain reaction technique we looked for microsatellite instability (MSI) as functional evidence of mismatch repair defects in 71 cases of acute myeloblastic leukaemia (AML). MSI was assessed at 11 loci in matched leukaemic and constitutional DNA. Nine out of 71 patients (13%) were found to have MSI. Four of these patients had therapy-related leukaemia and the remaining five were all over the age of 60 years. There was a high incidence of adverse-risk cytogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
3
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
(56 reference statements)
1
33
3
1
Order By: Relevance
“…Genomic instability in AML has led to a search for MSI in AML patients, but the results are quite controversial. While several studies have reported MSI in AML [9][10][11][12][13], a study of 132 cases failed to confirm the previous observations [14]. Although reasons for the discrepancy are unclear, the use of different microsatellite markers and different stages (i.e., diagnosis and relapse) of the disease may have contributed to the differences observed.…”
Section: Introductioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Genomic instability in AML has led to a search for MSI in AML patients, but the results are quite controversial. While several studies have reported MSI in AML [9][10][11][12][13], a study of 132 cases failed to confirm the previous observations [14]. Although reasons for the discrepancy are unclear, the use of different microsatellite markers and different stages (i.e., diagnosis and relapse) of the disease may have contributed to the differences observed.…”
Section: Introductioncontrasting
confidence: 50%
“…Thus, the identification of MSI in AML ( Figure 3A and Refs. [9][10][11][12][13]) suggests a complete loss of the MMR function in a significant fraction of leukemic cells in AML patients. Therefore, we believe that the observation of both wild type and mutant alleles in MSH2 and MLH1 amplicons is not due to heterozygous mutation of the genes, but the presence of both MMR proficient and deficient leukemic cells in the samples analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Matched leukemic and constitutional DNA was investigated for MSI using a panel of 11 microsatellite markers as described in Das-Gupta et al 12 A patient was considered to have MSI if a shift in the band pattern of the leukemic DNA was measured when comparing to reference constitutional DNA from the same patient.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…Results from these studies vary but generally the incidence of MSI is low in de novo AML: 0-10%, [9][10][11] higher incidence has been reported in de novo AML in the elderly. 12 Estimates of the incidence of MSI in therapy-related AML (t-AML), which arises as a consequence of prior chemotherapy or radiotherapy, are much higher. We have found MSI in 44% of t-AML cases, 12 however, the figures in the literature vary greatly, the extremes of the estimates being 0% 11 and 94%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation